Nutritional assessment of trees and shrubs of a tropical (bms-t) very dry forest for cattle production - Apráez G., Edmundo; Gálvez C., Arturo Leonel; Navia E., Jorge Fernando (Revista de Ciencias Agrícolas, 2017)
We determined the nutritional quality of the tree species: Pithecellobium lanceolatum Mart., Guazuma ulmifolia Lam., Cassia fistula L., Pithecellobium dulce Mart., and Samanea saman Jacq. in a Tropical very dry forest in Patía Valley, as well as their effect as a supplement in the nutrition of Cebu cattle. Six treatments were assessed: T0 (100% grazing); T1 (90% grazing+10% P.lanceolatum); T2 (90% grazing+10% P.dulce); T3 (90% grazing+10% S.saman); T4 (90% grazing+10% C. fistula), and T5 (90% grazing+10% G. ulmifolia), distributed in a Randomized Complete Block design. The phenology, nutritional content, and secondary metabolites of the trees were assessed. The highest contents of dry matter (47.1%), crude protein (23.5%), neutral detergent fiber (58%), and net energy (523 Kcal/100 g) were found for S. saman. FDA was greatest (p<0.05) in P. lanceolatum and G. ulmifolia with 39.5%. C. fistula and S. saman showed the lowest secondary metabolites levels. Saponins were detected in P. lanceolatum, P. dulce, P. lanceolatum, and G. ulmifolia. These species also showed low steroid content levels and none of these contained alkaloides. C. fistula and G. ulmifolia intake was low, at just 10g/day, while the other species were consumed at 100g/day. The greatest weight gain was obtained with S. saman (560g/day), while weight loss was observed with C. fistula (-20g/day). The highest weights during the rainy season were: C. fistula (1.7kg), S. saman and G.ulmifolia (1.36kg), P. lanceolatum (0.9kg), and P. dulce (0.36kg).